Parameter calibration and experimental verification of discrete element simulation model for Protaetia brevitarsis larvae bioconversion mixture - Li, Yuanze; Xie, Jianhua; Zhang, Jia; Yue, Yong; Meng, Qinghe; Du, Yakun; Ma, Deying (International Journal of Agricultural and Biological Engineering, 2024)
To improve the survival rate of larvae during material separation after biotransformation of existing residual film mixtures of Protaetia brevitarsis larvae, this paper adopts the method of combining physical test and EDEM simulation test, and selects Hertz Mindlin with JKR contact model to calibrate the discrete element simulation contact parameters of the Protaetia brevitarsis larvae and the frass mixture. First, the cylinder lifting method was used to determine the actual repose angle of the mixture of larvae and frass. The collision recovery coefficients between larvae-frass and steel, static friction coefficient, kinetic friction coefficient and the collision recovery coefficient between larvae were measured through physical tests such as the inclined plane method. The Plackett-Burman test was then used to screen out the factors that have a significant impact on the repose angle: Poisson’s ratio of frass, frass-frass rolling friction coefficient, frass JKR surface energy, frass-larvae JKR surface energy. The optimal value intervals of four significant factors were determined based on the steepest climb test, Based on the Box-Behnken response surface analysis test, the second-order regression model between the repose angle and four significant factors was determined, and variance and interaction effects were analyzed. And with the actual repose angle as the goal, the significant factors were optimized and the optimal parameter combination of the four significant factors was determined. The simulation test of material repose angle and screening was carried out with the optimal parameter combination, and compared with the physical test. It was found that the maximum relative errors of the two tests were 1.48% and 3.79% respectively, indicating that the calibrated parameter values are true and reliable, It can provide a reference for the discrete element simulation of the transportation and separation of the Protaetia brevitarsis larvae-frass mixture. Key words: Protaetia brevitarsis larvae-frass mixture; repose angle; parameter calibration; discrete element; model DOI: 10.25165/j.ijabe.20241704.8707 Citation: Li Y Z, Xie J H, Zhang J, Yue Y, Meng Q H, Du Y K, et al. Parameter calibration and experimental verification of discrete element simulation model for Protaetia brevitarsis larvae bioconversion mixture. Int J Agric & Biol Eng, 2024; 17(4): 35–44.